James Thomas papers - Thomas, James (Surveyor)
Survey of the Northern Neck of Virginia commissioned by the proprietor, Lord Thomas Fairfax.
Surveyor.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Fairfax, Thomas Fairfax, -- Lord, -- 1692-1782.; Northern Neck (Va.) -- Surveys; Virginia -- Surveys; Surveyors